The Effect Of Work Life Balance And Organizational Citizenship Behavior On Turnover Intention With Job Satisfaction As A Mediation Variable At Pt Pelayaran Bahtera Adhiguna - Qadriaty, Dina Laila; Wibowo, Imam; Latukismo, Tatag Herbayu (Dinasti Publisher, 2026)
This study aims to determine and analyze the direct and indirect effects of work-life balance, organizational citizenship behavior, and job satisfaction on turnover intention. The study was conducted at PT Pelayaran Bahtera Adhiguna with a sample of 66 respondents. The sampling technique used was simple random sampling. The data analysis method used descriptive analysis. The results showed that work-life balance, organizational citizenship behavior, and job satisfaction have a direct impact on turnover intention; job satisfaction cannot mediate work-life balance and organizational citizenship behavior on turnover intention.